An Investigation of Executive Functions and Cognitive Emotion Regulation in Labor Children Undergoing Training at Educational Centers - Kashani, Shamim Razaghi; Mashhadi, Ali; Farahi, Seyed Mohammad Mahdi Moshirian (European Scientific Journal, ESJ, 2017)
The aim of this study is to determine the comparison of executive functions and cognitive emotion regulation between labor children undergoing training at educational centers and normal children. The sample included 29 male children (mean=9.58, SD=0.50) which was selected from a childcare center. For the control group, 27 third-grade children were selected from a normal primary school (mean= 9.40, SD=0.50). Two questionnaires were used: 1-The extended version of executive function deficiency in everyday life (Barkley, 2011); 2-The child version of cognitive emotion regulation (Garnefski et al., 2007). Part one of this study showed that the scale of executive functions revealed that labor children under training in educational institutions were significantly different in terms of self-direction and time management and self-organization from normal children. Part two of this study showed that there is a significant reverse relationship between planning refocusing, self-regulation, and time management (r value < 0.05). Moreover, there was a significant reverse relationship between positive reappraisal and spontaneity (r value < 0.01), and a significant negative relationship between positive reappraisal and executive functions (r value < 0.05). Overall, it can be posited that children undergoing training in educational institutions are not different from normal children in terms of cognitive emotion regulation.